Phytoremediation with Brassicaceae and Apiaceae in soils contaminated with heavy metals - Salamanca-Rivera, Angela Patricia; Silva, Diego Alejandro; Cardozo-Muñoz, Juan; Rojas-Sánchez, Fabián; Meléndez-Mazabel, Juan Camilo; Borda-Chingate, Luis Santiago (Revista de Biología Tropical, 2023)
Introduction: The middle basin of the Bogotá River has been suffering from heavy metal contamination due to industrial discharges. This water source has been used to irrigate short-cycle crops, which has resulted in heavy metal contamination of productive soils. Objective: To evaluate a phytoremediation process with the plant species Broccoli (Brassica oleracea var. Italica plenck) and Cilantro (Coriandrum sativum L.) in soils contaminated with heavy metals in Mosquera, Colombia. Methods: Sampling was performed with a completely randomized factorial design: a) cilantro/broccoli proportions (30 cilantro/70 broccoli, 50/50, 70 cilantro/30 broccoli and two monoculture type controls of each species) and b) phytoremediation time (3, 6 and 9 months), each treatment with four experimental plots. Soil and plant tissue were analyzed in the laboratory by atomic absorption spectrophotometry to determine the concentration of heavy metals. Results: The analysis of heavy metals through of a spectrophotometric technique such as atomic absorption allowed the acquisition of data on concentrations, variations in relation to pH, movement of metals from soils to plant tissues and bioavailability in terms of concentration in bioaccumulator species such as Broccoli and Cilantro. In addition, the correlation matrices, and p-values lower than 0.05 allowed us to show significant data. Conclusions: Phytoremediation by means of Brassica oleracea var. Italica plenck and Coriandrum sativum L in 70/30 or 30/70 proportions in soils with pH between 5.5 and 6.0 allows a good recovery of soils with heavy metal contents in terms of high concentrations in short terms, starting bioremediation after three months and ending loads of variable availability after nine months. Result: The analysis of heavy metals by means of a spectrophotometric technique such as atomic absorption allowed the acquisition of data on concentrations, variations in relation to pH, movements of metals from soils to plant tissues and bioavailability in terms of concentration in bioaccumulative species. such as Broccoli and Cilantro. Additionally, correlation matrices and p-values less than 0.05 allow evidence of significance data. Conclusions: Phytoremediation by means of the species Brassica oleracea var. Italica plenck and Coriandrum sativum L in proportions 70/30 or 30/70 to soils with a pH between 5.5 and 6.0 allow a good recovery of soils with heavy metal content in terms of high concentrations in the short term, initiating bioremediation at the three months and ending variable availability loads after nine months.